Artificial Intelligence Adoption by Enterprises: Quantitative Research from Poland - Ludmiła FILINA-DAWIDOWICZ; Agnieszka BARCZAK; Joanna SĘK; Piotr TROJANOWSKI; Anna WIKTOROWSKA-JASIK; Dorota CIESIELCZYK (Communications of International Proceedings, 2025)
Artificial intelligence (AI) technologies are increasingly developed and adopted in enterprises. This trend is also observed in Poland. However, current implementation of these technologies is impacted by the number of challenges and concerns. The article aims to investigate the opinions of practitioners on the AI adoption in enterprises in Poland. The questionnaire survey was used to conduct the quantitative research. Opinions of practitioners employed in enterprises in Poland were collected between February and July 2025. Research results analysis revealed that almost 50% of surveyed practitioners use AI in companies. The reasons for not using AI include lack of human resources or knowledge, high implementation costs and concerns on data protection. In turn, the most of surveyed practitioners pointed out that AI is implemented for process automation or decision-making support. Within the areas of activity in which AI technologies are applied in enterprises, respondents highlighted work organization and office tasks, marketing or sales support, and production or service delivery support. Respondents perceive saving time and costs, as well as error and risk reduction as the greatest benefits in implementing AI. The concerns on AI implementation largely refer to possibility of errors occurrence and dependence on technology. The majority of practitioners expressed optimistic viewpoint about rapid and moderate adoption of AI in enterprises over the next 10 years.
Keywords: Artificial intelligence (AI); modern technologies; enterprises; digital transformation; Poland.